Distribution of University Admission Quotas: Problems of Competitive Selection Process - L. M. Nurieva; S. G. Kiselev (Образование и наука)
Introduction. Nowadays, an important criterion for the effectiveness of vocational education is the demand for graduates in the labour market. In order to ensure maximum compliance of the structure of training of specialists with the needs of the economy in personnel, the Ministry of Education and Science of theRussian Federation annually establishes admission quotas in universities on the basis of regional development forecasts. However, one of the options for the distribution of admission quotas in recent years has become an inter-university competition, as a result of which budget places are transferred to educational institutions only on the basisindicators of their effectiveness, i.e. excluding the dynamics of local labour markets. While the problems of coordination of admission quotas and the need for personnel are sufficiently covered in the literature, the mechanism of the distribution of places in the competition has been insufficiently studied so far.The aim of this research was to analyse the mechanism of competitive distribution of admission quotas on the example of higher education institutions, which provide training for bachelor and specialist programmes in the field of “Education and Pedagogical Sciences”.Methodology and research methods. The present research is based on the methodology of integrated research, including the methods of comparative and statistical analysis of data, their systematisation and generalisation.Results and scientific novelty. It is shown that the process of distribution of admission quotas is generated in accordance with the official competitive selection methodology. The study established that none of the indicators applied in the calculations of the effectiveness of universities’ activities were statistically related to the results of the competition. The main reason for the inability of the competitive mechanism to carry out the correct ranking of participants in terms of success is the major methodological and mathematical errors inherent in the algorithms for determining the effectiveness of educational organisations. As a result, the number of budget places allocated to each university is largely determined by chance. The results of the competitive distribution of admission quotas depend only on the industry sector of educational institutions. The widespread development of the idea of quoting of budgetary education on indicators of an interuniversity competition will inevitably aggravate a disproportion problem between territorial training and demand for them in regions. There will certainly be a deficiency of young specialists due to low mobility of graduates of the Russian higher school and reduction of the contingent of provincial higher education institutions-outsiders. Conversely, the personnel surplus will appear in the regional educational institutions (mainly metropolitan), which won the competitions. The proposals on correction of the evolving negative socio-economic situation are formulated.Practical significance. The authors believe that the research results will make it possible to thoroughly discuss the rectilinear projection of effective outcome monitoring in higher education institutions for competitive distribution of admission quotas and the feasibility of holding a competition in general. Moreover, the results of the present study contribute to the method of competitive distribution of university admission quotas.